Effects of Sustainability Report on Organization Performance: A Study Based on Listed Companies in ASEAN - ปินตา นิธิภักดิ์ (Journal for Developing the Social and Community, 2016)
The objectives of this study were to (1) study the effects of Sustainability report on organization performance of the listed companies in the Stock Exchange of ASEAN, (2) to compare the organization performance between DJSI group and Non-DJSI group and (3) to examine if the organization performance is influenced by firm characteristics – net revenue, firm size and financial leverage. Organization performances including net profit margin, return on assets and return on equity were analyzed. Sustainability Reports are evaluated on the basic of firms included in Dow Jones Sustainability Index. Samples were divided into two groups which are a group of 50 firms belonging to DJSI and a group of 50 firms not on the DJSI (Non-DJSI), in total 100 firms. Data were collected from the 2014 financial statements and annual reports. T test was used for means comparison, simple linear regression was employed for analysis the effects of sustainability report on organization performance and multiple regression analysis were used for examine firm characteristics. The study results showed that organization performance including Net profit Margin, Return on Assets (ROA) and Return on Equity (ROE) for DJSI group and for Non DJSI group were not different at a 5% significance level. It also showed that the sustainability report has no impact on organization performance. Moreover, the study demonstrated that financial leverage was negatively and significantly related to organization performance. However, there were no link between net revenue, firm size and organization performance.